Effects of Ozone Treatment on Personal Protective Equipment Contaminated with SARS-CoV-2 - Clavo, Bernardino (Antioxidants (Basel), 2020)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is causing profound health, economic, and social problems worldwide. Management of personal protective equipment (PPE) and its potential limited availability have created concerns about the increased risks for healthcare professionals at hospitals and nursing homes. Ozone is a powerful oxidant agent. The objectives of this study were to examine the effects of ozone treatment on PPE contaminated with SARS-CoV-2, and to explore whether relative humidity could modify those effects. Methods: PPE contaminated by heat-inactivated SARS-CoV-2 were treated with different ozone concentrations, exposure times, and relative humidity conditions. SARS-CoV-2 gene amplification was assessed by real-time polymerase chain reaction. Results: There was no amplification of SARS-CoV-2 in PPE after the following ozone exposures: 30 s at 10,000 ppm (20 g/m(3)), 5 min at 4000 ppm, and 10 min at 2000 ppm. At lower ozone concentrations, 4–12 ppm (0.008–0.024 g/m(3)), the effects were highly dependent on the relative humidity conditions. Conclusions: Oxidative stress induced by ozone exposure eliminated heat-inactivated SARS-CoV-2 in different PPE components under appropriate exposure times, ozone concentrations, and relative humidity conditions. These findings could have implications in decreasing the risk of contamination associated with personal protective equipment management and in increasing its availability. Further research in the original SARS-CoV-2 strain is guaranteed.